Room temperature Z-selective hydrogenation of alkynes by hemilabile and non-innocent (NNN)Co(ii) catalysts - Sharma, Dipesh M.; Gouda, Chandrakant; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2022)
Hemilabile and phosphine-free quinolinyl-based NNN-type pincer and non-pincer cobalt complexes were developed for the room temperature catalytic transfer semi-hydrogenation of alkynes to Z-alkenes. Treatment of the quinolinyl-amine ligand, [C9H6N(NH)CH2CH2NEt2] ((NNN2NEt2)-N-Q-N-CH)-H with CoX2 afforded the pincer complexes kappa(3)-((NNN2NEt2)-N-Q-N-CH)CoX2 (X = Cl, Br), whereas, the quinolinyl-amide ligand, [C9H6N(NH)C(O)CH2NEt2] ((NNNNEt2)-N-Q-N-C(O))-H gave chelate anionic complexes kappa(2)-((NN)-N-Q)CoX2((NHNEt2)-H-C(O)) (X = Cl, Br). The well-defined anionic non-pincer cobalt complexes efficiently catalyzed the semi-hydrogenation of diverse alkynes to deliver highly chemoselective and stereodivergent Z-alkenes at room temperature. This hydrogenation exhibited broad substrate scope with the tolerance of sensitive functional groups, such as -Cl, -Br, -I, -OH, -NH2, -COOMe, and pyridinyl, employing a stable and user-friendly ammonia borane hydrogen source.

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung